2010
DOI: 10.1111/j.1744-1609.2010.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of practice guideline dissemination and implementation strategies for healthcare teams and team-based practice

Abstract: Team-based care using practice guidelines locally adapted can affect positively patient and provider outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
2
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 99 publications
(137 reference statements)
4
64
2
6
Order By: Relevance
“…Speech pathologists indicated that educational meetings, educational resources, and support from colleagues were or would be the most useful strategy to assist with guideline implementation. This contrasts the extensive review on other health professionals where providing reminders was the most commonly reported effective strategy, followed by audit and feedback, opinion leaders, and educational outreach visits [18-20]. Speech pathologists in this study reported reminders to be the least effective strategy which was not expected.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…Speech pathologists indicated that educational meetings, educational resources, and support from colleagues were or would be the most useful strategy to assist with guideline implementation. This contrasts the extensive review on other health professionals where providing reminders was the most commonly reported effective strategy, followed by audit and feedback, opinion leaders, and educational outreach visits [18-20]. Speech pathologists in this study reported reminders to be the least effective strategy which was not expected.…”
Section: Discussioncontrasting
confidence: 89%
“…These facilitators were also reported by health professionals such as physicians, nurses, and occupational therapists previously [18-20,22,26,45]. Teamwork is a significant factor that influences the successfulness of stroke rehabilitation training programs and hence patient outcomes, such as functional gains [46] and length of hospital stay [47].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations